(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The long Spanish exile, one of the direct consequences of the Franco regime, brought about the progressive and ruthless loss of most leading republicans, a lot of them in Mexico, which turned into their new homeland. This was also the case of the socialist leader Indalecio Prieto Tuero, who lived in the Mexican capital and died there on the morning of 12 February 1962. This article discusses how the Mexican press treated and assessed the death of this politician whose political and journalistic career created a strongly impact and who was respectfully called “Don Indalecio” by the press.